Human guanylate binding proteins potentiate the anti-chlamydia effects of interferon-gamma. - Illya Tietzel; Christelle El-Haibi; Rey A Carabeo (PLoS ONE)
Chlamydiae are obligate intracellular pathogens that are sensitive to pro-inflammatory cytokine interferon-gamma. IFN-gamma-inducible murine p47 GTPases have been demonstrated to function in resistance to chlamydia infection in vivo and in vitro. Because the human genome does not encode IFN-gamma-inducible homologues of these proteins, the significance of the p47 GTPase findings to chlamydia pathogenesis in humans is unclear. Here we report a pair of IFN-gamma-inducible proteins, the human guanylate binding proteins (hGBPs) 1 and 2 that potentiate the anti-chlamydial properties of IFN-gamma. hGBP1 and 2 localize to the inclusion membrane, and their anti-chlamydial functions required the GTPase domain. Alone, hGBP1 or 2 have mild, but statistically significant and reproducible negative effects on the growth of Chlamydia trachomatis, whilst having potent anti-chlamydial activity in conjunction with treatment with a sub-inhibitory concentration of IFN-gamma. Thus, hGBPs appear to potentiate the anti-chlamydial effects of IFN-gamma. Indeed, depletion of hGBP1 and 2 in cells treated with IFN-gamma led to an increase in inclusion size, indicative of better growth. Interestingly, chlamydia species/strains harboring the full-length version of the putative cytotoxin gene, which has been suggested to confer resistance to IFN-gamma was not affected by hGBP overexpression. These findings identify the guanylate binding proteins as potentiators of IFN-gamma inhibition of C. trachomatis growth, and may be the targets of the chlamydial cytotoxin.